Development of an empirical correlation for Newtonian and non-Newtonian fluids in a stirred tank reactor, to predict oxygen mass transfer rates - Raposo, Sara (2014)
Most of animal and plant cell cultures present a non-Newtonian behaviour that has a deep effect on the technological performance of bioreactors, affecting the pattern of mixing, the power input required and on the mass and energy transfer as well. In aerobic cultures, the oxygen mass transfer is still a bottleneck, particularly at industrial scale-up, where the high-cell-density biomass and production of metabolites provoke the increase on the viscosity culture, lowering the production yield and eventually losing economical process viability.